Cases and materials on the law of the sea - Sohn, Louis B.; Noyes, John E., 1951-; Franckx, Erik, 1957-; Juras, Kristen Gustafson (Leiden : Brill Nijhoff, 2014)
This second edition of Cases and Materials on the Law of the Sea compiles cases, treaties, U.N. documents, commentaries, and other teaching materials that systematically present law of the sea topics.
TOC
Includes index.
law
Ershad
Keywords: Law of the sea; Casebooks (Law)